An academic and regional nurse research collaborative: Implications for nursing research. Issue 6 (26th October 2022) - Lombardo, MaryJo Carter; Mackay, Periwinkle; Stavarski, Debra Haas; Alderfer, Mary Ellen; Dutton, Suzanne; Scala, Elizabeth; Gerstenhaber, Melissa
Abstract: Introduction: A diverse group of nurses and research Network Coordinators formed a collaboration to advance nursing research within Johns Hopkins Clinical Research Network, a partnership of academic and community hospitals in the mid‐Atlantic region. The purpose of the Nurse Research Collaborative (NRC) is to provide mentoring, mutual growth, and assist the health care organizations to fulfill nursing research requirements. Background: We created a multiinstitutional nursing research organization with diversity of member participants and health care facilities. The NRC structure allowed nonacademic facilities to engage in a variety of nursing research projects. This allows for increases in study sample sizes of diverse populations to support and expand nursing research. The NRC is modeled after a physician clinical research network with an aligned mission, vision, goals, and strategic priorities across member organizations. Main Ideas: To strengthen multiinstitutional nursing research capability, the NRC developed an infrastructure of leadership, regular meetings, and formal educational presentations. The NRC completed three research studies, facilitating the Institutional Review Board application process, reviewing documents and contracts, providing individual institutional support, and coordinating site leader functions. Conclusion: A research collaboration of nurses, across multiple hospitals provides efficiencies and expertise not otherwise available in every organization.